Shear and micro-shear bond strengths of four self-etching adhesives measured immediately and 24 hours after application - Choltacha Harnirattisai (2018)
This study measured the immediate and 24 h shear (SBS) and micro-shear bond strengths (MSBS) to dentin of four self-etching adhesives. A resin composite was bonded using each adhesive to the area of 5-mm diameter for SBS test or 0.75-mm diameter for MSBS test of flat bovine dentin. The bond strengths of all adhesives at 10 min were lower than at 24 h for both tests. The mean SBS (MPa, 10 min, 24 h) were similar in ranking order at both time periods that is: Clearfil SE Bond (21.2, 25.3) > Clearfil TriS Bond (12.7, 19.5)=i Bond (11.7, 19.5)=G Bond (11.1, 16.6). For the MSBS test, G Bond provided equivalent mean bond strength (35.0) to Clearfil SE Bond (36.9) and higher than the other adhesives at 24 h [i Bond (26.3), Clearfil TriS Bond (28.5)]. In conclusion, the MSBS test was slightly more discriminating than the SBS test.